Antioxidant effects of pineapple vinegar in reversing of paracetamol-induced liver damage in mice - Mohamad, Nurul Elyani; Swee, Keong Yeap; Kian, Lam Lim; Mohd Yusof, Hamidah; Boon, Kee Beh; Sheau, Wei Tan; Wan, Yong Ho; Sharifuddin, Shaiful Adzni; Jamaluddin, Anisah; Long, Kamariah; Nik Abd Rahman, Nik Mohd Afizan; Alitheen, Noorjahan Banu (BioMed Central, 2015)
BACKGROUND: Pineapple (Ananas comosus) was demonstrated to be hepatoprotective. This study aims to investigate the reversing effects of pineapple vinegar on paracetamol-induced liver damage in murine model.